Motivasi Belajar Siswa Pada Pembelajaran Sains: Studi Komparasi Pada Tiga Sekolah - Deka Hermiati; Ogi Danika Pranata; Hendra Lardiman (UNIB Press, 2024)
This research aimed to provide a general overview of students' learning motivation in science at the junior high school level and to compare the level of learning motivation among students from three different schools: SMPN 27 Kerinci, MTsN 1 Sungai Penuh, and MTsS Siulak in the 2023/2024 Academic Year. The sample for this research consisted of 72 students, with 24 students from each school. The research utilized descriptive and comparative methods. Data on students' learning motivation were collected through the Students' Adaptive Learning Engagement in Science Questionnaire and analyzed descriptively and comparatively using the Kruskal-Wallis test. The results indicate that, overall, students exhibit high motivation to learn science, scoring 4.10 on a scale of 5.00. Additionally, students from the three different schools also demonstrated high average learning motivation, with scores of 4.26 (SMP N 27 Kerinci), 4.15 (MTsS Siulak), and 4.01 (MTsN 1 Sungai Penuh). Despite these differences, the Kruskal-Wallis statistical test revealed that the variations were not statistically significant (ρ=0.09). Furthermore, when examining each indicator separately, only one indicator, namely self-regulation (ρ=0.008), showed a significant difference. This distinction in self-regulation was influenced by students' perceptions regarding tasks in science learning, including their views on effort, persistence, punctuality, and a lack of discrimination regarding the form of tasks to be completed.